Detection of genetic markers associated with resistance to pathogens in ayocote beans from Puebla, Mexico - Ruiz-Salazar, Regulo; Vargas-Vázquez, María Luisa Patricia; Hernández-Delgado, Sanjuana; Muruaga-Martinez, José S.; Mayek Perez, Netzahualcoyotl (Revista Mexicana de Ciencias Agrícolas, 2019)
Ayocote beans (Phaseolus coccineus L.); 2n= 2x= 22) is a legume native to the highlands of Mexico, it is important in human nutrition and detection of improvement characteristics, it shows resistance to pathogens and certain abiotic factors that cause losses in the bean crop. With the premise of identifying Phaseolus germplasm with multiple resistance to biotic and abiotic adverse factors, this work was carried out with the objective of this work was to determine the resistance or susceptibility to two important pathogens: common blight [Xanthomonas axonopodis pv. phaseoli (Smith)] and anthracnose [Colletotrichum lindemutianum Sacc. & Magn (anamorph Glomerella lindemuthiana Shear)] based on the identification of sequences characterized by amplified regions (SCARs). The study included 117 accessions collected at different sites in Puebla, Mexico (region called Carso Huasteco), which were analyzed with 10 SCAR markers (six markers for common blight: SAP6, BAC6, SU91, LG5, R7313, R4865, four for anthracnose: SAS13, SBB14, SAB3, SH18) at the Center for Genomic Biotechnology in Reynosa, Tamaulipas. The SAS13 and SBB14 anthracnose resistance markers are present more frequently (89 and 74%), followed by the common blight resistance markers BAC6 and SU91 (74 and 42%). The germplasm of Zacapoaxtla and Tlatlauquitepec had a higher frequency of SCARs (Zacapoaxtla: 90% and 100% for SAS13 and SBB14; Tlatlauquitepec: 94% and 56%). Accessions with five SCARs could be used as a source of resistance to diseases in Phaseolus and early and late genotypes to flowering and physiological maturity, as well as variables in testa color, pod size and seed, but no association was detected between the presence of SCARs with the morphology of ayocote beans.
Keywords: : Colletotrichum lindemuthianum; Phaseolus pathogens and Xanthomonas axonopodis pv. Phaseoli; Carso Huasteco